2022
DOI: 10.1262/jrd.2021-120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on the endometrial epidermal growth factor profile and fertility in dairy cows

Abstract: The endometrial epidermal growth factor profile is an indicator of uterine function and fertility in cattle. The present study aimed to investigate the effects of heat stress on the endometrial EGF profile and fertility in lactating Holstein cows. The endometrial EGF profiles of 365 cows in the Hokkaido and Kyushu regions were examined between June and September (heat stress period, n = 211) and between October and January (control period, n = 154). EGF profiles were investigated using uterine endometrial tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Epidermal growth factors (EGF) in the endometrium are critical for reproduction in mammals [ 37 , 38 ], including dairy cows [ 39 ]. Moreover, high parity [ 40 ] and heat stress [ 41 ] increase the risk of EGF abnormalities in dairy cows. Another theory is that lipopolysaccharide (LPS), an endotoxin produced by gram-negative bacteria, reduces gonad receptivity to hormonal stimulation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factors (EGF) in the endometrium are critical for reproduction in mammals [ 37 , 38 ], including dairy cows [ 39 ]. Moreover, high parity [ 40 ] and heat stress [ 41 ] increase the risk of EGF abnormalities in dairy cows. Another theory is that lipopolysaccharide (LPS), an endotoxin produced by gram-negative bacteria, reduces gonad receptivity to hormonal stimulation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the stress from overheating of an organism, the concentration of cortisol also increases. Cortisol is a stress hormone from the adrenal gland, which inhibits the implantation of the embryo into the uterine wall and causes early loss of embryos [10,11]. An ovulated oocyte from an inferior follicle shows signs of inferior quality; it has lower fertility; therefore, several inseminations are required for successful fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Many embryos fail soon after fertilization, when they have only two or four cells. During the fi rst few days after fertilization, the embryos are much more sensitive to heat stress than at a later stage, when their own ability to adapt has already developed [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study found that the group of cows that experienced HS (THI of ≥ 73) 3 weeks before insemination had more unfertilized oocytes than the control (21% vs. 4%, respectively), a lower conception rate, and reduced embryo development during the first 16 gestational days [ 17 ]. Moreover, HS can affect endometrial functions, e.g., prostaglandin and protein secretion [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%